Między Chrystusem a ziemskimi pożądliwościami. Historia przekładów i interpretacji oraz współczesna debata nad ewokacją ho emos eros estaurotai (Rom 7, 2) Ignacego Antiocheńskiego - Abucewicz, Krzysztof (Vox Patrum, 2015)
Composed into the letter of Ignatius of Antioch to the Church of Rome, perhaps the most famous evocation – ho emos eros estaurotai – has a long tradition of interpretation, which being initiated by Origen and taking somewhat turbulent course reaches our times. Its manifestation is visible in the translations themselves, where already from the Latin rendering a significant diversity can be observed, and the wide range of interpretations is being reflected with its spread in the modern translations. Those of Greek Fathers who spoke after Origen essentially upheld the interpretation of the Alexandrian, seeing under eros – as he did – the Christ Himself. Finally they fastened so conceptualized eros in the spiritual theology and inscribed the Ignatius’ evocation into the liturgy of the Eastern Church for ages. However in the Western Church, it seems that the significant influence on the modern interpretation of the Ignatius’ evocation – starting from the nineteenth century – had the ongoing in the background discussion on authenticity of the Antiocher’s letters. The time of extensive research, beyond the contribution to the determination of the middle recension, from exacting blade of critics had adjudicated about fundamental error of Origen and the other Greek Fathers in the interpretation they adopted. The dominance of the newly discovered interpretation coincided with the adoption of middle recension and spreads to the present day. The resulting dissonance to the voice of the ancient Church born an undying question which – although with different intensity at different times – continues resounding. Could the Greek Fathers be so much wrong in taking the comment to the famous Ignatius’ evocation? How is it possible that those for whom the ancient Greek was the language of everyday life, and appropriate for the letters of Ignatius „Sitz im Leben” was the environment in which in the chronological proximity they grew up and lived, diverge from the actual socio-cultural and literary context from the inside of which Ignatius spoke? These and other questions have intrigued many scholars of the last century. It is, perhaps, their echo that outlines a certain circle being formed by modern translations and commentaries, running back to the beginning, to the first interpretations. This movement, presumably, shows unextinguished disagreement for leaving such a significant dissonance to the voice of the ancient Church. Perhaps it is also a hunch that in the content of the Ignatius’ words there is still something else, what more clearly saw the Fathers, and what in some sense remains hidden from modern researchers. By the same token, following the path of these assumptions, the undertaken analysis of the Syrian translation combined with the conclusions of the recent philological study on the Greek text put a question mark on the popular interpretation and allow to hypothesize in a way that is getting closer to the voice of Fathers again. It seems that the meaning of Ignatius’ evocation could have been more positive than it is used to be frequently commented.